• 2022-06-04
    lim(x→∞)(1-1/(x+1))^(-x-1)=lim(x→∞)(1/(x+1))^(-x-1)lim(x→∞)(1-1/(x+1))^(x+1)
  • lim(x→∞)(1-1/(x+1))^(-x-1)=lim(x→∞)(1+1/(-x-1))^(-x-1)=e,这是因为x→∞,-x-1→∞.再根据下面这个极限lim(x→∞)(1+1/x)^x=e

    内容

    • 0

      【单选题】若 f ( x ) = ( x − 1 ) x 2 − 1 2 , g ( x ) = x − 1 x + 1 ,则? A. f ( x ) = g ( x ) "> f ( x ) = g ( x ) B. lim x → 1 f ( x ) = g ( x ) "> lim x → 1 f ( x ) = g ( x ) C. lim x → 1 f ( x ) = lim x → 1 g ( x ) "> lim x → 1 f ( x ) = lim x → 1 g ( x ) D. 以上等式均不成立

    • 1

      求极限lim(x→1)(2/x^2-1)-(1/x-1)

    • 2

      曲线y=xln(e+1/x)(x>0)的渐近线为()。 A: x=1/e,y=x+1/e B: x=-1/e,y=x+1/e C: x=1/e,y=x-1/e D: x=-1/e,y=x-1/e

    • 3

      (1)lim(x-1)/sin(x-1),x趋向于1

    • 4

      为什么lim(x→∞)(1-1/x)^3=1?